Flexibility and Differentiation: A Plea for allowing National Differentiation in the Fundamental Rights Domain - DE VISSER, Maartje (Institutional Knowledge at Singapore Management University, 2017)
The subject of the protection of fundamental rights today is a mainstay in EU legal studies, as a cursory glance at the table of contents of leading textbooks and journals in the field attests. Debates about the proper role of the Union institutions, and in particular that of the Court of Justice (CJEU), in respecting and upholding such rights have been taking place ever since the seminal rulings in Stauder and Internationale Handelsgesellschaft, which established that the EU institutions must heed the fundamental rights that form an integral part of the general principles of Union law. The Lisbon Treaty has given a fresh impetus to the academic discourse on EU fundamental rights, by prescribing the Union’s accession to the European Convention on Human Rights (ECHR) and by granting the Charter of Fundamental Rights, first proclaimed at Nice in December 2001, binding force. In keeping with the theme of this book, the aim of the present chapter is to consider whether, in a legal landscape characterised by the presence of several interlocking rights instruments, it is desirable for the CJEU to allow the Member States to offer a higher degree of fundamental rights protection than is required under EU law. To this end, the chapter opens with a tour d’horizon of modalities for interaction and conflict resolution envisaged by each of the different rights regimes that co-exist within the European legal sphere, against the backdrop of insights from the literature on constitutional pluralism (Section 2).